Thermal characteristics and product formation mechanism during pyrolysis of penicillin fermentation residue. (April 2019) - Wang, Zhiqiang; Hong, Chen; Xing, Yi; Li, Zaixing; Li, Yifei; Yang, Jian; Feng, Lihui; Hu, Jiashuo; Sun, Haipeng
Graphical abstract: Highlights: Higher heating rate significantly improved the pyrolysis performance of penicillin fermentation residue (PR). Each stage of PR pyrolysis can be described by corresponding kinetic models. N gaseous species such as NH3 and HCN produced due to the decomposition of proteins in PR. Large quantities of N-heterocyclic compounds in bio-oil were formed at higher temperatures. Abstract: This work studied thermal characteristics and product formation mechanism during pyrolysis of penicillin fermentation residue (PR). Results showed that PR pyrolysis proceeded in four stages. The kinetic triplet of each stage was calculated using Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, and integral master-plot methods. The kinetic model for stage 1 was the three-dimensional diffusion model, the simple reaction order model for stage 2 and stage 4, and the nucleation-growth model for stage 3. FTIR analysis suggested that the intensities of absorption peaks of NH, CO, CH, CN, and CO in chars weakened gradually with increasing temperature, corresponding to the production of CH4, CO, NH3, and HCN. GC-MS results indicated that the high protein content in PR resulted in a high fraction of nitrogenated compounds (amides and amines, nitriles, and N-heterocyclic species) in bio-oil. The formation mechanism of these compounds was discussed. Besides, bio-oil also contained large quantities of oxygenated compounds and a few hydrocarbons.